Geodesy : introduction to geodetic datum and geodetic systems - Lu, Zhiping; Qiao, Shubo; Qu, Yunying (Springer, 2014)
Geodetic datum (including coordinate datum, height datum, depth datum, gravimetry datum) and geodetic systems (including geodetic coordinate system, plane coordinate system, height system, gravimetry system) are the common foundations for every aspect of geomatics. This course book focuses on geodetic datum and geodetic systems, and describes the basic theories, techniques, methods of geodesy. The main themes include: the various techniques of geodetic data acquisition, geodetic datum and geodetic control networks, geoid and height systems, reference ellipsoid and geodetic coordinate systems, Gaussian projection and Gaussian plan coordinates and the establishment of geodetic coordinate systems. The framework of this book is based on several decades of lecture noted and the contents are developed systematically for a complete introduction to the geodetic foundations of geomatics.